2018
DOI: 10.1002/lary.27651
|View full text |Cite
|
Sign up to set email alerts
|

Is greater antibiotic therapy prior to ESS associated with differences in surgical outcomes in CRS?

Abstract: Objective Antibiotics have been a mainstay of chronic rhinosinusitis therapy; however, data suggest that antibiotics may also result in several adverse unintended consequences. We aimed to evaluate if greater antibiotic use prior to sinus surgery was associated with differences in surgical outcomes. Methods Adult CRS patients enrolled in a prospective, multi‐institutional, observational cohort study were asked to recall systemic antibiotic use in the 90 days prior to endoscopic sinus surgery (ESS). Antibiotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…One study found preoperative antibiotic use led to significantly better SNOT scores but not endoscopic scores, especially in the rhinologic subset. However, the high antibiotic dose group (more than 29 days out of 90 days prior to ESS) was relatively less improved 1961 . In addition, macrolide therapy was reported effective 1105,1121,1962 .…”
Section: Surgery For Chronic Rhinosinusitismentioning
confidence: 92%
“…One study found preoperative antibiotic use led to significantly better SNOT scores but not endoscopic scores, especially in the rhinologic subset. However, the high antibiotic dose group (more than 29 days out of 90 days prior to ESS) was relatively less improved 1961 . In addition, macrolide therapy was reported effective 1105,1121,1962 .…”
Section: Surgery For Chronic Rhinosinusitismentioning
confidence: 92%
“…25,26 In contrast, 27.9% to 36.4% of respondents would choose an antibiotic that did not reduce SSI risk at all compared with no antibiotic. This decision may indicate blind preferences for antibiotics, misconceptions about improved postsurgical outcomes, 27 or a desire to ameliorate family members' or individual concerns. 25 This behavior highlights the need to improve patient education to inform accurate risk perceptions, 28 and optimize antibiotic use moving forward.…”
Section: Discussionmentioning
confidence: 99%
“…The need for systemic medications indicates poor disease control both because of what it may reflect (greater disease severity or AECRS) but also a direct risk of harm to the patient through the impact of side effects and adverse events. Previous study of systemic medication use for CRS has revealed novel insights into the clinical course of CRS and also revealed the use of antibiotics and oral corticosteroids for CRS is a distinct aspect of the CRS disease course (12,(34)(35)(36) . However, patient-reported, CRS-related antibiotics and oral corticosteroids usage has not been validated as a metric for CRS disease burden.…”
Section: Discussionmentioning
confidence: 99%
“…The EPOS 2012 criteria describe CRS-related systemic antibiotic usage and systemic corticosteroid usage in the prior 3 months as elements of CRS disease control. Moreover, patient-reported usage of systemic antibiotics and corticosteroids for CRS have been previously described as outcome measures in various studies (22)(23)(24)(25) . However, the frequency of patient-reported systemic antibiotic or corticosteroid usage has not been fully validated as both valid and responsive measures of CRS disease burden.…”
Section: Introductionmentioning
confidence: 99%